Penerapan Teknologi Tepat Guna Filtrasi Air Payau Skala Rumah Tangga di Wilayah Pesisir Kampung Bugis dan Senggarang, Kota Tanjungpinang - Audi Aqila; Ashar Saputra; Johan Syafri Mahathir Ahmad; Irvan Wahyu Muhammad; Puspita Dewi Cahyani (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
Kampung Bugis and Senggarang in Tanjungpinang City are coastal areas that face serious challenges in accessing clean water, primarily due to the high salinity of groundwater, which results in water that is turbid, odorous, and unsuitable for domestic use. This condition highlights the need for the application of simple, affordable, and easily operated technological solutions that do not rely on large-scale clean water supply systems. This community service program aims to implement Appropriate Technology (AT) in the form of a household-scale brackish water filtration system as an effort to improve clean water quality while empowering coastal communities to manage their water resources independently and sustainably. The program was conducted as part of the 2025 UGM Community Service Program (KKN-PPM) using a participatory approach that actively involved community members at all stages of implementation, including water condition surveys, system design and assembly, installation of the filtration unit, training on operation and maintenance, and performance evaluation. The filtration system was designed using fiberglass tanks filled with layered filtration media consisting of silica sand, manganese, activated carbon, and micron filters, which function to reduce turbidity, odor, and excessive mineral content in brackish water. The results of the program demonstrated a significant improvement in water quality, as indicated by changes from previously turbid and odorous water to clear and odorless water, as well as pH values and total dissolved solids approaching national clean water quality standards. The community showed positive responses and high enthusiasm in operating and maintaining the filtration system, as it was considered effective, user-friendly, and suitable for local conditions. In addition to providing technical benefits, the program also enhanced collective awareness of the importance of clean water management and environmental health. Overall, the implementation of household-scale brackish water filtration as Appropriate Technology proved to be effective, adaptable, and highly replicable in other coastal areas with the support of local governments and active community participation.